Christ Church, Durham Parish, Md., records - Christ Church (Durham Parish, Md.)
One volume of 92 positive photostats and 1 bundle of 92 negative photostats reproducing volume 1 (1774-1824) of the Christ Church vestry book, and one bundle of positive copyflow copies reproducing volume 2 (1824-1927). Includes minutes of church business meetings, calendars of church activities, petitions, oaths, and a last will and testament copied into the Church record.
Microfilm edition available
Photocopies produced from originals in the Durham Parish, Christ Church, Maryland.
Collection material in English.
Keywords: Church records and registers -- Maryland; Charles County (Md.) -- Church history; Episcopal Church